Estrogen and Progesterone Receptor Gene Expression During Different Stages of Uterine Involution in Sahel Goats - Bukar Majama, Yagana; Abdulsalam, Hassan; Burah, Shettima; Bakari Mahre, Mohammed; Danladi Kwari, Hyelduku (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The study investigated estrogen and progesterone receptor gene expression during different stages of uterine involution in sahel goats. Thirty-five Sahel does (30) and bucks (5) (2-3.5 years and 30-40 kg) were used for the study. Pregnancies were achieved by natural mating after synchronization. Repeated injection of cloprostenol at 250μg/kg intramuscularly were given at 11- day interval. The does were randomly separated into postpartum days 1,3,7,14, 21 and 28 to undergo ovariohysterectomy for uterine tissue sample collection through caesarean section. Collected tissues were fixed in 10% formalin and used for estrogen and progesterone ELISA assay using commercial kits. The results showed that, the concentration of progesterone receptor on day 1 was 5.15 ± 1.01 ng/ml, followed by progressive decrease on day 3 and 4 postpartum, and a fluctuating trend in increase between day 14, 21 and 28. The highest peak (26.6 ± 2.21 ng/L) concentration of estrogen receptor was observed on day 7 postpartum and significantly (p < 0.05) decrease to 17.4ng/L on day 28 postpartum. Conclusively, the concentration of progesterone and estrogen receptor protein at the various stages of uterine involution indicate that upregulation of these receptors were carried out by progesterone and estrogen.